Mobility of Hellenistic women - Loman, Pasi (2004)
The purpose of the current thesis is to study various aspects of women’s mobility in the so-called Hellenistic period. It will attempt to provide answers to the questions ‘why did women travel,’ ‘how common was it for women to travel,’ and most importantly, ‘did women take part in the Hellenistic colonisation processes.’ The importance of women’s mobility for the Greek societies as a whole will also be evaluated.